Incidence and mortality trends of male breast cancer in selected areas of Anhui province, 2010 - 2020: a cancer registry-based analysis - Dan DAI; Qiang ZHU; Wei XU; Yili LYU; Tingting DOU; Huadong WANG; Qinglian MENG (Zhongguo gonggong weisheng, 2025)
ObjectiveTo analyze the incidence and mortality trends of male breast cancer in Anhui province from 2010 to 2020 based on cancer registry data, with the aim of developing prevention and control strategies for breast cancer in the population. MethodsData on male breast cancer cases registered in Anhui province from 2010 through 2020 were collected from the China Cancer Registry Platform or the CANREG 4 system. The age- and area-specific number and rate of incidence and mortality, as well as the age-standardized incidence and mortality rates of male breast cancer, were calculated. The Joinpoint model was used to estimate the annual percentage change (APC) in these indicators to analyze the trends in incidence and mortality of male breast cancer in selected areas with cancer registration in the province during this period. ResultsFor the population covered by the cancer registration in the province during the study period, the crude incidence rate (per 100 000) of male breast cancer was 0.58 (0.53 and 0.61 for urban and rural populations, respectively), and the age-standardized incidence rate was 0.44 (0.38 and 0.49 for urban and rural populations, respectively). There was no significant changing trend in the age-standardized incidence rate for the total population (APC = –1.17%, P > 0.05) or for both urban and rural populations (APC = –0.24% and –2.59%, respectively, both P > 0.05). The crude mortality rate of male breast cancer was 0.21 for the total population, with 0.20 and 0.21 for urban and rural populations, respectively. The age-standardized mortality rate was 0.14 for the total population, with 0.13 and 0.16 for urban and rural populations, respectively. There were no significant changing trends in the age-standardized mortality rate for the total population (APC = 3.08%, P > 0.05) or for the rural population (APC = 0.83%, P > 0.05), but there was a significant upward trend in the age-standardized mortality rate for the urban population (APC = 6.29%, P = 0.003). ConclusionsThe registered mortality rate of male breast cancer in the urban population of Anhui province showed an increasing trend from 2010 to 2020, suggesting that more attention should be given to the prevention and control of male breast cancer in urban areas.